THE RELATIONSHIP OF CARPAL TUNNEL SYNDROME CLINICAL SYMPTOMPS AND ELECTRONEUROMYOGRAPHY RESULTS IN RSSA MALANG - Kurniawan, Shahdevi Nandar; Husna, Machlusil; Rasyid, Harun Al; Bilqis, Nadiya Elfira (Malang Neurology Journal, 2016)
Background. Carpal tunnel syndrome (CTS) is caused by entrapment neuropathy of the median nerve in the carpal tunnel that can be detected with electroneuromyography (ENMG).Objective. To determine whether there are significant differences in parameters of ENMG examination between CTS groups with mild-to-moderate and severe clinical symptoms.Methods. The study design was observational analytic using cross sectional design approach of the patient's medical record data as many as 61 samples.Results. From 61 samples, there were dominancy of age â‰¥ 40 years old as many as 80.32% and gender female as many as 88.52%. There was no significant differences in age and gender between the two groups (p=0.073 and p=1.000 respectively). Sensory amplitude, MSDL, and Ring Diff are significantly different between the two groups (p=0.005, p=0.020, and p=0.031 respectively). There are no significant difference of motor amplitude and MMDL between the two groups (p=0.384 and p=0.196 respectively).Conclusion. Sensory amplitude value having a relationship with the severity of clinical symptoms. ENMG examination and clinical symptoms of CTS were independent parameters, that should not be used alone to make a diagnosi both of them could enhance the accuracy of diagnosis.